2017
DOI: 10.1002/ange.201708305
|View full text |Cite
|
Sign up to set email alerts
|

Treten in der N‐heterozyklischen Carben‐Organokatalyse wirklich Carbene auf?

Abstract: In der Organokatalyse werden häufig Azolium-Kationen in Anwesenheit einer Base eingesetzt, um wertvolle Syntheseschritte zu realisieren. Aufgrund der Annahme,d ass durch Deprotonierung des Kations ein freies Carben entsteht, welches mit dem Substrat reagiert und somit dessen Reaktivität entscheidend beeinflusst, werden Reaktionen dieses Types als N-heterozyklische Carben-Katalyse bezeichnet. Wirk çnnen hier jedochz eigen, dass ein Mechanismus,i nd em das Azolium-Kation analog der elektrophilen aromatischen Sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…As for many ILs, the investigation of the hydrogen bond dynamics is hindered by the interference due to the ionicity , of the system ranging from charge transfer or polarization to the formation of neutral species. In the case of the imidazolium cation, this means that carbene formation, with additional hydrogen bonds as acceptors, or even carbene catalysis can play a role. On top of this, the HBs in imidazolium-based ILs are donated by a carbon ring atom and are therefore of a relatively weak type. , …”
Section: Introductionmentioning
confidence: 99%
“…As for many ILs, the investigation of the hydrogen bond dynamics is hindered by the interference due to the ionicity , of the system ranging from charge transfer or polarization to the formation of neutral species. In the case of the imidazolium cation, this means that carbene formation, with additional hydrogen bonds as acceptors, or even carbene catalysis can play a role. On top of this, the HBs in imidazolium-based ILs are donated by a carbon ring atom and are therefore of a relatively weak type. , …”
Section: Introductionmentioning
confidence: 99%
“…In this regard, it was observed that compared with the structuring and dynamics within the pure IL, the addition of water to [C 2 C 1 Im]­[OAc] modifies and widely disturbs the dipole moment of the ions and the hydrogen bond network of the IL. Furthermore, it hinders a possible carbene formation, besides the fact that a free carbene is not likely. ,, Feng and Voth investigated the effect of the side chain length of the cation and the effect of the anion, for the IL–water mixtures of 1-butyl-3-methylimidazolium tetrafluoroborate ([C 4 C 1 Im]­[BF 4 ]), 1-octyl-3-methylimidazolium tetrafluoroborate ([C 8 C 1 Im]­[BF 4 ]), and 1-octyl-3-methylimidazolium chloride ([C 8 C 1 Im]­[Cl]) with water mole fractions ranging from 0.2 to 0.9615, on the mixture dynamics and structures . While replacing [C 4 C 1 Im] + by [C 8 C 1 Im] + only leads to an increasing microheterogeneity due to a stronger agglomeration of the cations, exchanging [BF 4 ] − for [Cl] − results in a decrease in the diffusion due to stronger electrostatic interactions between [Cl] − and water as compared with the relatively weakly coordinating anion [BF 4 ] − .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it hinders a possible carbene formation, besides the fact that a free carbene is not likely. 33,58,59 Feng and Voth investigated the effect of the side chain length of the cation and the effect of the anion, for the IL−water mixtures of 1-butyl-3-methylimidazolium tetrafluoroborate…”
Section: ■ Introductionmentioning
confidence: 99%